2020
DOI: 10.1001/jamaoncol.2020.1694
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Minimally Invasive vs Open Radical Hysterectomy for Early-Stage Cervical Cancer

Abstract: IMPORTANCE Minimally invasive techniques are increasingly common in cancer surgery. A recent randomized clinical trial has brought into question the safety of minimally invasive radical hysterectomy for cervical cancer.OBJECTIVE To quantify the risk of recurrence and death associated with minimally invasive vs open radical hysterectomy for early-stage cervical cancer reported in observational studies optimized to control for confounding. Ovid MEDLINE, Ovid Embase, PubMed, Scopus, and Web of Science (inception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
106
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(127 citation statements)
references
References 79 publications
7
106
4
1
Order By: Relevance
“…Decreased survival outcomes with minimally invasive radical hysterectomy, which were demonstrated in a recent meta-analysis of 15 studies, are particularly concerning. 6 As endorsed by the study team, it is paramount to be aware that open radical hysterectomy is the gold standard surgical treatment for women with early cervical cancer.…”
Section: Gynecological Cancermentioning
confidence: 99%
“…Decreased survival outcomes with minimally invasive radical hysterectomy, which were demonstrated in a recent meta-analysis of 15 studies, are particularly concerning. 6 As endorsed by the study team, it is paramount to be aware that open radical hysterectomy is the gold standard surgical treatment for women with early cervical cancer.…”
Section: Gynecological Cancermentioning
confidence: 99%
“…Treatment of early-stage disease (clinical International Federation of Gynecology and Obstetrics (FIGO) stage IA1-IB1 and IIA1) is represented by radical hysterectomy and pelvic lymphadenectomy with sentinel lymph node (SLN) biopsy (Cibula 2018 ). After the publication of a randomized controlled trial, which demonstrated an inferior survival outcome if patients with early-stage cervical cancer were treated with minimally invasive, compared to open radical hysterectomy (Ramirez 2018 ), multiple retrospective studies showed a survival difference between the two approaches, with consequent recommendations amendment by international societies (Koh 2019 ; Nitecki 2020 ; Querleu 2020 ), particularly for tumors larger than 2 cm (Pedone Anchora 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, their efforts to assess how manipulator use and vaginal closure may modify the magnitude of the associations between minimally invasive hysterectomy and adverse survival outcomes is an important step in elucidating the factors that may mediate these effects. While some recent well-designed observational studies have not found an association between minimally invasive radical hysterectomy and recurrence or death, 17 18 the majority of such studies [6][7][8][9][10][11][12][13][14][15] have found evidence of harm. The SUCCOR study delivers another significant blow to a surgical paradigm that is increasingly difficult to justify in routine clinical practice.…”
mentioning
confidence: 99%
“…[2][3][4][5] In addition to LACC, these guidelines have cited a growing literature of adequately powered, well-designed observational studies that, overall, have had concordant results. [6][7][8][9][10][11][12][13][14][15] In this issue of the International Journal of Gynecological Cancer, Chiva and colleagues 16 present additional evidence of the deleterious effect of minimally invasive radical hysterectomy, and suggest possible mechanisms underlying this association. The SUCCOR study is a large, retrospective, observational cohort study that evaluates associations between surgical approach and survival outcomes among women with International Federation of Gynecology and Obstetrics (FIGO) 2009 stage 1B1 cervical cancer within 126 institutions in 29 European countries.…”
mentioning
confidence: 99%